Loading test of full-scale composite plate girder with partial encasing. (March 2023) - Yi, Jiwoon; Park, Jang Ho; Park, Wonsuk; Choi, Daehun; Choo, Jinkyo F.
Abstract: Plate girders have been extensively studied to propose improved or updated configurations for coping with instability as well as constructability problems. Yet, this study introduces a new configuration of the composite plate girder which encases the upper part of the steel plate girder in the concrete slab and the trimming of the upper outer corner of the vertical stiffeners to accommodate temporary cross-beams during the erection and ease the installation of forms without the need of propping. Rather than using corrugated webs, the proposed girder utilizes only flat plates to simplify its fabrication and allow camber to be provided through an automated manufacturing process so that high quality standards can be achieved. The proposed configuration has enough flexural buckling strength with minimum horizontal stiffeners and only 2 plate thicknesses, which promotes purchase efficiency of the steel plate and accelerates production of the girder. A 51 m-long full-scale composite plate girder was fabricated and subjected to fatigue test up to 2 million cycles followed by ultimate strength test. The prototype remained sound beyond the ultimate limit state and did not suffer any noticeable damage or loss of flexural rigidity until the end of the test. A finite element model was also established to overcome the limitations of the test facility and validate the design of the composite girder. The comparison of the experimental and analytical results revealed good agreement and demonstrated remarkable fatigue resistance. The proposed composite plate girder satisfied sufficiently the relevant design requirements. Highlights: Partial encasing of girder in concrete proposed for novel plate girder bridge Easier and safer construction by trimming of upper corner of vertical stiffeners Faster and eco-friendly manufacture by automated fabrication and painting facility Fatigue test up to 2 million loading cycles on full scale 51 m-long prototype Improved flexural rigidity, lateral stability and reduced depth of superstructure